Melatonin Protects Neural Stem Cells Against Tri-Ortho-Cresyl Phosphate-Induced Autophagy - Liu, Chang; Zhou, Wenjuan; Li, Zhaopei; Ren, Jun; Li, Xian; Li, Shan; Liu, Qian; Song, Fuyong; Hao, Aijun; Wang, Fuwu (Frontiers in Molecular Neuroscience, 2020)
Tri-ortho-cresyl phosphate (TOCP) is an extensively used organophosphate in industry. It has been proved to lead to toxicity in different organ systems, especially in the nervous system. Neural stem cells (NSCs) play important roles in both embryonic and adult nervous systems. However, whether TOCP induces cytotoxicity in embryonic NSCs remains unclear. In this study, mouse NSCs were exposed to different concentrations of TOCP for 24 h. The results showed that TOCP induced the autophagy of NSCs by increasing the generation of intracellular reactive oxygen species and decreasing the phosphorylation of extracellular regulated protein kinase (ERK1/2). Melatonin has been reported to exert neuroprotective effects via various mechanisms. Therefore, we further investigate whether melatonin had potential protective effects against TOCP-induced cytotoxicity on NSCs. Our data showed that melatonin pretreatment attenuated TOCP-induced autophagy by suppressing oxidative stress and restoring ERK1/2 phosphorylation consistently. Taken together, the results indicated that TOCP induced the autophagy in mouse NSCs, and melatonin may effectively protect NSCs against TOCP-induced autophagy.